Comparative brain anatomy of human and non-human primates: a review (Research, Society and Development, 2021)
The anatomical study of non-human primates has played an important role in clinical and surgical interventions in veterinary medicine. It is known that the most well-known experimental model in the scientific area is the Macaca mulatta, popularly known as the Rhesus monkey, and what the literature has demonstrated are new experimental models that can supply studies on the central nervous system, making it necessary for these discoveries to deepen greater in the area of comparative anatomy. The purpose of this literature review is to promote a broad view of the anatomical aspects of the brain of human and non-human primates in comparative terms. In this review, some peculiarities were observed in non-human primates regarding the path of blood vessels in the brain, as well as the presence of different venous sinuses of the dura when compared to the human primate. The importance of the morphological study regarding the anatomy of the telencephalon, as well as the mechanisms of lining, cerebral arterial irrigation and drainage of the venous sinuses of the dura mater, provides information on the brain organization of non-human primates, data that are scarce in the literature scientific, but that generate subsidies for understanding other areas of ethological and functional investigations, when compared to the human primate.